2014
DOI: 10.1053/j.gastro.2013.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Rifaximin Alters Intestinal Bacteria and Prevents Stress-Induced Gut Inflammation and Visceral Hyperalgesia in Rats

Abstract: Background & Aims Rifaximin is used to treat patients with functional gastrointestinal disorders, but little is known about its therapeutic mechanism. We propose that rifaximin modulates the ileal bacterial community, reduces subclinical inflammation of the intestinal mucosa, and improves gut barrier function to reduce visceral hypersensitivity. Methods We induced visceral hyperalgesia in rats, via chronic water avoidance or repeat restraint stressors, and investigated whether rifaximin altered the gut micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
210
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(232 citation statements)
references
References 46 publications
(50 reference statements)
6
210
2
3
Order By: Relevance
“…18,20,21 However, our current study is in agreement with several other studies involving laboratory rodents that have failed to find a significant effect of stressor exposure on fecal or luminal lactobacilli levels. 19,42,43 However, the finding that colonic mucosa-associated lactobacilli are reduced in mice exposed to the chronic restraint stressor is consistent with a previous study in as little as one 2-hour exposure to a social stressor significantly reduced the relative abundance of colonic mucosa-associated Lactobacillus in C57BL/6 and CD-1 mice. 44 Thus, it is apparent that stressor exposure reduces mucosa-associated, but not luminal, lactobacilli in laboratory mice.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…18,20,21 However, our current study is in agreement with several other studies involving laboratory rodents that have failed to find a significant effect of stressor exposure on fecal or luminal lactobacilli levels. 19,42,43 However, the finding that colonic mucosa-associated lactobacilli are reduced in mice exposed to the chronic restraint stressor is consistent with a previous study in as little as one 2-hour exposure to a social stressor significantly reduced the relative abundance of colonic mucosa-associated Lactobacillus in C57BL/6 and CD-1 mice. 44 Thus, it is apparent that stressor exposure reduces mucosa-associated, but not luminal, lactobacilli in laboratory mice.…”
Section: Discussionsupporting
confidence: 90%
“…22,39,40 Some studies suggest that changes to the microbiota could be involved in stressor-induced GI immune dysfunction, but stressor-induced changes in gut microbiota have not been well-characterized. 41,42 In this study, mice were exposed to a widely used and well-validated murine model of chronic stress to elucidate the effects of a long-term stressor upon the colonic microbiota. The data show that microbial communities associating with colonic tissue and found in the lumen of the colon have unique community structures that are differentially impacted by psychological stressor exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies linking the gut microbiota with visceral sensitivity, have shown that increments in the Lactobacilli family (during probiotic treatment or during states of dysbiosis) are associated to visceral analgesic-like states. 18,19,21,33 In our conditions, we can speculate that the moderate increment in Lactobacillus spp. counts observed in antibiotic-treated animals might be important in the observed visceral pain-related responses.…”
Section: Discussionmentioning
confidence: 53%
“…All these bacteria have been implicated in both GI physiology and pathology. 18,21,26,[31][32][33] Recent evidences suggest a key role of some bacterial groups in immune functions (mainly segmented filamentous bacteria, SFB, and Clostridia from the clusters XIVa and VI) which are, in normal conditions, in direct contact to the host and, therefore, directly influencing host immune responses. 19,[34][35][36] In agreement with this, we found Clostridia, SFB, and Enterobacteria adhered, in large percentages, to the colonic epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…While the use of some antibiotics has been associated with the development of IBS, poorly-absorbed antimicrobials such as rifaximin may still be of benefit. 70 The mechanism of action is largely unclear but rifaximin has been used successfully in several double-blind, placebo-controlled trials to improve symptoms of bloating and flatulence. However, one needs to exercise caution given the risk of developing resistant organisms.…”
Section: B Lactis B Bifidum) Lactobacillus Acidophilus Andmentioning
confidence: 99%